Nd2O3, Cr2O3, and V2O3 Nanoparticles via Calcination: Synthesis, Characterization, Antimicrobial and Antioxidant Activities. (6th July 2022) - Al-Fakeh, Maged S.; Al-Otaibi, Najla F.
Abstract : Nd2 O3, Cr2 O3, and V2 O3 nanoparticles were prepared by calcining the precursor materials that are novel mixed ligand complexes: [Nd(BDC)(ADMPY)(OAc)].H2 O, [Cr(BDC)(ADM PY)Cl].H2 O, and [V(BDC)(ADMPY)Cl].H2 O, where BDC = 1, 4-benzenedicarboxylic acid and ADMPY = 2-amino-4, 6-dimethyl pyrimidine. The generated compounds were examined through several techniques such as elemental analysis (C.H.N), UV-Vis spectroscopy, thermal analysis (thermogravimetric, differential thermogravimetry, and differential thermal analysis), FT-IR spectra, X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscope (TEM). The TEM micrographs showed that neodymium oxide nanoparticles assumed agglomerated platelet-like particles, with particle sizes around 30.16 nm, while chromium oxide NPs showed solid block material with compact density and fewer pores with nearly spherical shape and 56.12 nm size. The vanadium oxide NPs were an agglomeration of small spherical nanoparticles of 28.4 nm size. The antimicrobial properties of the samples were assessed using two strains of Gram-positive bacteria, two strains of Gram-negative bacteria, and one strain of yeast. The antimicrobial results demonstrated that a large spectrum of activity characterizes the tested compounds because they are active on Gram-positive and Gram-negative bacteria, especially on Gram-positive strains. The antioxidant activity of prepared compounds was assessed by scavenging free radicals of DPPH. Metal oxide NPs also showed promising results as antioxidants.